Avaliação do pH de oxidação do processo fenton na remoção de microcistina-LR de água de abastecimento - Silva, Aluízio Gonçalves da (2015)
Algal blooms and toxic cyanobacteria in fountains intended for human supply has been reported in many countries in recent decades due to impacts and human actions in the most diverse ecosystems on the planet. The presence of lineages of cyanobacteria producing cyanotoxins has negative effects on water bodies in particular in the intendend to the public supply due to the harmful effect of these substances on human health and animals. In general, cyanotoxins are not removed by conventional purifying water technologies. This study aimed to evaluate the efficiency of advanced oxidation process with the Fenton reagent in the oxidation of microcystin-LR water for public supply using conventional treatment steps coagulation, flocculation and sedimentation. The study water was prepared by adding the lysed cell cultivation Microcystis aeruginosa dechlorinated with potable water. Oxidation steps were performed, coagulation, flocculation and sedimentation JarTest programmed with rapid mixing -1 time of 10 s, rapid mixing gradient of 1000 s , flocculation time 20 min, flocculation gradient -1 -1 30 s and sedimentation velocity 1,4 cm.min . Different pH ranges were tested (2,0, 4,5 and + 7,0) and different concentrations of the Fenton reagent in the proportion of 1/3 H2O/Fe . The obtained results showed the oxidation of microcystin-LR in the treatments with pH 2,0; 4,5; and 7,0. By scanning the ions in the mass spectrometer it was possible to identify the peaks of mass/charge (m/z) fragments of enabling confirmation of oxidation by the presence of oxidation by products. Furthermore, after sedimentation the Fenton reagent enables significant removal being treatment T2 in time of 15 minutes the best for include percentage removal of turbidity 0,07 uT, true color 2,61 uH, COD 7,7 mg.L and MC-LR 0,07 μg.L.